Chemical Regulation of DNA i‐Motifs for Nanobiotechnology and Therapeutics. Issue 10 (29th January 2019) - Debnath, Manish; Fatma, Khushnood; Dash, Jyotirmayee
Abstract: DNA sequences rich in cytosine have the propensity, under acidic pH, to fold into four‐stranded intercalated DNA structures called i‐motifs. Recent studies have provided significant breakthroughs that demonstrate how chemists can manipulate these structures for nanobiotechnology and therapeutics. The first section of this Minireview discusses the development of advanced functional nanostructures by synthetic conjugation of i‐motifs with organic scaffolds and metal nanoparticles and their role in therapeutics. The second section highlights the therapeutic targeting of i‐motifs with chemical scaffolds and their significance in biology. For this, first we shed light on the long‐lasting debate regarding the stability of i‐motifs under physiological conditions. Next, we present a comparative analysis of recently reported small molecules for specifically targeting i‐motifs over other abundant DNA structures and modulating their function in cellular systems. These advances provide new insights into i‐motif‐targeted regulation of gene expression, telomere maintenance, and therapeutic applications. Abstract : Non‐canonical DNA structures : i‐Motifs are four‐stranded DNA structures formed by the folding of cytosine‐rich sequences present in telomeres and gene promoters. Compared to complementary G‐quadruplexes, i‐motifs are less explored. This Minireview describes significant advances in chemically regulated i‐motif‐based functional nanostructures and small‐molecule targeting of i‐motifs for therapeutics.